Guidelines for Lung Bamboo (Bambusa longissima sp. nov.) Propagation by Offsets and Planting - Nguyen, V.T.; Nguyen, K.L.; Manh, L.K. (2020)
This manual aims to support people who work in bamboo forestry with the propagation of Lung bamboo using offset planting. The manual offers step-by-step guidelines for the selection of sites for Lung clump mother plants, techniques for detaching offset planting, planting, maintenance and protection.